Implementation of Fullover Training Towards The Improvement of Badminton Smash Corresponding with The Covid 19 Health Protocol - Irsan Kahar; Firmansyah Dahlan; Syahruddin Syahruddin; Suaib Nur (IKIP Budi Utomo Malang, 2021)
There are 2 problems which become the urgency in this research; student activity unit for badminton is a new sports medium, thus it needs improvement in training forms, one of the training form is the improvement of smash basic skill. The aims of this research are to discover the influence of fullover training towards badminton smash basic skill , and also applying the research and training process which correspond with Covid 19 health protocol. This research is an experiment type. Independent variable (badminton smash basic skill) dependent variable (fullover training). Sampling technique used saturated sample wich is all the population of badminton student activity unit at UM Palopo which are 20 atlethes. Test instrument used smash basic skill test. Time and place corresponded with WFH( work from home), research processes (pre test, treatment, post test) were monitored online through Zoom meeting and UM Palopo E-learning . The results of hypothesis test found that t-count 3,647 bigger than t-table 1,833 at the 5% significancy or 0,05. according to the hypothesis test, it can be concluded that Fullover training influence the badminton smash basic skill.